Immune tolerance induction in severe haemophilia A: A UKHCDO inhibitor and paediatric working party consensus update. Issue 6 (17th August 2021) - Hart, Daniel P.; Alamelu, Jayanthi; Bhatnagar, Neha; Biss, Tina; Collins, Peter W.; Hall, Georgina; Hay, Charles; Liesner, Ri; Makris, Michael; Mathias, Mary; Motwani, Jayashree; Palmer, Ben; et al.
Abstract: Introduction: In good risk patients (historic inhibitor peak < 200BU), the International Immune Tolerance Study demonstrated equal efficacy to induce tolerance between high (200iu/kg/day) and low dose (50iu/kg ×3 times/week) immune tolerance induction (ITI) regimens. However, the trial stopped early on account of the excessive bleed rate in the low dose ITI arm. Methods: United Kingdom Haemophilia Centre Doctors' Organization (UKHCDO) Paediatric and Inhibitor working parties considered available ITI data alongside the bi‐phenotypic antibody emicizumab (Hemlibra®) efficacy and safety data to develop a consensus guideline for the future UK ITI guideline. Results: This revision of UKHCDO ITI guidance incorporates the recommendation to use emicizumab as a prophylaxis haemostatic agent to reduce bleeding rates and to facilitate low dose and reduced frequency of FVIII CFC for ITI in the majority of children. Conclusion: This consensus protocol will facilitate future evaluation of ITI outcomes in the evolving landscape of haemophilia therapeutics and ITI strategies.